Exploring the Role of Parenting in Shaping Adolescent Mental Health: A Review of Literature - Fitrio Deviantony; Salwa Nirwanawati (Jurnal Kesehatan Komunitas Indonesia, 2025)
Background: Adolescence is an important period in a person's life, during which many physical, emotional, and social changes occur. During this time, adolescents often face mental health issues such as stress, anxiety, and depression, especially when they have difficulty adjusting to the changes. Parenting strongly influences adolescents' mental health, as it can help them cope with problems, increase their self-confidence, and maintain their emotional well-being. Aims: This study aims to investigate the impact of parenting on adolescents' mental health, examining both the positive and negative effects, and identifying the most effective approach to support adolescents' mental well-being. Methods: This study employed a literature review of articles published between 2019 and 2024. The articles were selected from various sources, including Google Scholar and PubMed. The selection process resulted in 10 articles relevant to this topic. Results: Research shows that parenting is closely related to adolescents' mental health. Authoritative parenting, which combines control with emotional support, can improve adolescents' mental well-being. Conversely, permissive or authoritarian parenting tends to be associated with mental health problems such as anxiety and depression in adolescents. Conclusion: Parenting has a significant influence on adolescents' mental health. Encouraging supportive parenting and providing space for self-development will help adolescents have better mental health.